2019
DOI: 10.1111/jan.14122
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and perceived social support: The mediating role of secondary traumatization in nurses vs. physicians

Abstract: Aims The study aimed to examine differences between paediatric nurses and physicians regarding burnout syndrome, secondary traumatic stress (STS) and perceived social support (PSS). Background Paediatric nurses and physicians encounter cumulative effects of treating sick and injured children and helping their families, in situations that might promote burnout and STS. Design Cross‐sectional design. Method Nurses (n = 158) and physicians (N = 76) completed self‐report questionnaires on STS, PSS and burnout. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 76 publications
(109 reference statements)
2
35
0
1
Order By: Relevance
“…It is common for healthcare professionals who must care for complex patients who require extensive care (such as the elderly with dementia) to experience reduced compassion satisfaction, increased compassion fatigue and burnout. Therefore, nurses suffer from more emotional burnout than other healthcare professionals [ 51 ]. It seems clear that the characteristics of the job, lack of time and the pressure to attend to patients, generate an impact on the mental health of nurses, which, if not properly managed, leads to chronic stress [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is common for healthcare professionals who must care for complex patients who require extensive care (such as the elderly with dementia) to experience reduced compassion satisfaction, increased compassion fatigue and burnout. Therefore, nurses suffer from more emotional burnout than other healthcare professionals [ 51 ]. It seems clear that the characteristics of the job, lack of time and the pressure to attend to patients, generate an impact on the mental health of nurses, which, if not properly managed, leads to chronic stress [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents answer through a 7‐point scale for each item. Internal reliability of the MSPSS in healthcare workers is good with α = >0.90 ( Hamama et al ., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…SLPs who feel overwhelmed can consider partnering with other educators to improve the number of social connections, while also attenuating the stress associated with a demanding caseload (Archibald, 2017;Zurawski, 2014). Working with other professionals can decrease the sense of isolation one might feel during bouts of overwhelm and increase a sense of connection (Bogue & Bogue, 2019;Hamama et al, 2019). Researchers have found that increased social interaction and support can strengthen the perception of one's ability to cope with their job demands (Hamama et al, 2019).…”
Section: Broad Examples To Reduce Overwhelmmentioning
confidence: 99%
“…Working with other professionals can decrease the sense of isolation one might feel during bouts of overwhelm and increase a sense of connection (Bogue & Bogue, 2019;Hamama et al, 2019). Researchers have found that increased social interaction and support can strengthen the perception of one's ability to cope with their job demands (Hamama et al, 2019). Starting small will be important here; collaborating with even one new teacher has the potential to make a difference.…”
Section: Broad Examples To Reduce Overwhelmmentioning
confidence: 99%